Analisis Kebutuhan Pengembangan Buku Ajar Berbasis Team Based Project di Mata Kuliah Perkembangan Peserta Didik - Kurnisar, Kurnisar; Waluyati, Sri Artati; Fatihah, Husnul (Journal of Moral and Civic Education, 2025)
A textbook is an essential learning resource that must be continuously developed to support effective teaching methods. One of the courses at Universitas Sriwijaya requiring such development is the Student Development Course (PPD). Based on preliminary studies, students across all PPKn study programs at Universitas Sriwijaya face difficulties in accessing textbooks that align with their learning needs, which negatively impacts their academic performance. If left unaddressed, this issue could hinder the achievement of course competencies. This research applied the ADDIE development model, consisting of five stages: 1) analysis, 2) product design, 3) product development, 4) product implementation, and 5) evaluation. The research subjects were students enrolled in the PPD course in the Indralaya class. The findings revealed that the project-based learning (PBL) textbook tested on students was more effective, as it was easier to understand and better suited to their learning requirements. However, the study's limitation lies in its focus on Universitas Sriwijaya students, making the findings less generalizable to other institutions with different student characteristics. Further research is recommended to evaluate the application of this textbook in a broader range of institutions and learning contexts.